Risk management and surveillance systems: A Model proposed for the provincial public hospital (CHP) - Khassouani Chems-Eddouha (EDP Sciences, 2021)
During the Covid-19 pandemic, the provincial hospitals (CHP) of Morocco have demonstrated a remarkable capacity for reactivity. They were able to reorganize themselves to ensure the response to the pandemic and maintain basic functions. However, this reactivity alone does not prove their resilience in the face of new infections and possible disasters. The CHP must plan its responsiveness well in advance by building an intra-hospital health vigilance system that meets basic provincial requirements and that communicates with its internal and external environments. A qualitative analysis, using the focus group method, on Ifrane hospital risk management system revealed that, the systems for notification and declaration of adverse events are set up under the responsibility of multiple actors and using multiple notification forms. The processes and procedures are not clear with an overlap between the activities of quality assurance, risk management and complaints treatment system. A lot of information does not arrive at its destination on time, which impacts decision-making. This work proposes a hospital risk management model with two systems, one for safety of care and the other for risk management, taking into account the missions of the CHP and the different sources of information.